Informação, conhecimento e transdisciplinaridade: mudanças na ciência, na universidade e na comunicação científica - Aleixina Maria Lopes Andalecio (2009)
This text presents discussions and results of a piece of doctoral research centered on the questions raised by the new forms of production and organization of knowledge, guided by the discourse and practice of transdisciplinarity. The latter is understood in the context ofthe university, as an effort to overcome the fragmentation of knowledge into disciplines and excessive specialization, in face of the complex reality of the modern world, with its relational and interconnected character. To guide the questions, the research is based on the presuppositions that there is an epistemological, practical, social and political distance between the discourse and practice of transdisciplinarity. The study is supported by three analytical and theoretical axes: a) knowledge and information; b) university; c) transdisciplinarity. The empirical field is represented by the analysis of two large institutional transdisciplinary projects implemented at the Federal University of Minas Gerais in the late 1990s, the Institute of Advanced Transdisciplinaries Studies - IEAT e o Projeto Manuelzão. In the methodology, indepth half-structured interviews were used. The interviews analysis was based on Grounded Theory methodology. The results reached found a strong discourse in favor of transdisciplinarity but the researchers still work in a disciplinary manner in practice. However, there seems to be a consensus that transdisciplinarity presents itself as an appropriate approach to dealwith complex problems.